Quantitative Descriptive Analysis - Sidel, Joel L; Bleibaum, Rebecca N; Tao, K.W. Clara (Descriptive Analysis in Sensory Evaluation, 2018)
The QDA method was first published in 1974 (Stone, et al.) introducing a procedure for quantifying sensory descriptive perception. The method also introduced several concepts new to descriptive testing including individual data rather than consensus opinion and graphic line scaling. QDA is consumer oriented in panel selection, training, and attribute language, and is useful for several product development and marketing activities including Product Optimization research. The following chapter describes several product applications, the evolution of QDA to Tragon QDA®, and Diagnostic Descriptive Analysis (DDA). It also describes the procedure, rationale, and behavioral science supporting the method.